Human foreskin fibroblasts: from waste bag to important biomedical applications. (November 2018) - Oliveira, Thomaz; Costa, Ilana; Marinho, Victor; Carvalho, Valécia; Uchôa, Karla; Ayres, Carla; Teixeira, Silmar; Vasconcelos, Daniel F P
Circumcision is one of the most performed surgical procedures worldwide, and it is estimated that one in three men worldwide is circumcised, which makes the preputial skin removed after surgery an abundant material for possible applications. In particular, it is possible efficiently to isolate the cells of the foreskin, with fibroblasts being the most abundant cells of the dermis and the most used in biomedical research. This work aimed to review the knowledge and obtain a broad view of the main applications of human foreskin fibroblast cell culture. A literature search was conducted, including clinical trials, preclinical basic research studies, reviews and experimental studies. Several medical and laboratory applications of human foreskin fibroblast cell culture have been described, especially when it comes to the use of human foreskin fibroblasts as feeder cells for the cultivation of human embryonic stem cells, in addition to co-culture with other cell types. The culture of foreskin fibroblasts has also been used to: obtain induced pluripotent stem cells; the diagnosis of Clostridium difficile ; to test the toxicity and effect of substances on normal cells, especially the toxicity of possible antineoplastic drugs; in viral culture, mainly of the human cytomegalovirus, study of the pathogenesis of other microorganisms; varied studies of cellular physiology and cellular interactions. Fibroblasts are important for cell models for varied application cultures, demonstrating how the preputial material can be reused, making possible new applications. Level of evidence: Not applicable for this multicentre audit.